2022
DOI: 10.1016/j.euo.2021.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Management of Treatment-emergent Hepatic Toxicity in Patients with Advanced Renal Cell Carcinoma Receiving First-line Pembrolizumab plus Axitinib. Results from the KEYNOTE-426 Trial

Abstract: Background: Pembrolizumab plus axitinib improved efficacy over sunitinib in treatment-naive advanced renal cell carcinoma in the KEYNOTE-426 (NCT02853331) study. However, a relatively high incidence of grade 3/4 aminotransferase elevations was observed. Objective: To further characterize treatment-emergent aminotransferase elevations in patients treated with pembrolizumab-axitinib. Design, setting, and participants: Patients enrolled in KEYNOTE-426 were included in this study. Outcome measurements and statisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…The course of the present case possibly indicated that cells in lesion#1 destroyed by axitinib triggered the immune system via antigen presentation and PD‐1/PD‐L1 suppression by pembrolizumab 8 . It is recently reported that median time to ALT elevation is 84.0 days (range: 7‐840 days) 9 . Delayed‐onset hepatitis (Day+629) appeared to support delayed immune activation.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The course of the present case possibly indicated that cells in lesion#1 destroyed by axitinib triggered the immune system via antigen presentation and PD‐1/PD‐L1 suppression by pembrolizumab 8 . It is recently reported that median time to ALT elevation is 84.0 days (range: 7‐840 days) 9 . Delayed‐onset hepatitis (Day+629) appeared to support delayed immune activation.…”
Section: Discussionmentioning
confidence: 84%
“…8 It is recently reported that median time to ALT elevation is 84.0 days (range: 7-840 days). 9 Delayedonset hepatitis (Day+629) appeared to support delayed immune activation. We previously experienced a case with metastatic RCC, who died of severe hepatotoxicity presumably due to nivolumab followed by pazopanib regardless of nivolumab withdrawal.…”
Section: Discussionmentioning
confidence: 99%
“…One hundred patients were rechallenged with one or both study treatment(s): 45/100 (45%) had ALT ≥ 3× ULN recurrence, and all 45 recovered to ALT < 3× ULN following study treatment interruption/discontinuation. [27] No other cases of MOF related to pembrolizumab-axitinib treatment are reported in literature; however, Nakazawa et al in 2022 reported a case of acute heart failure in a woman treated with lenvatinib plus pembrolizumab for a clear cell endometrial carcinoma. [28] The patient was treated with highdose steroids and made a full recovery, but the treatment with pembrolizumab and lenvatinib was discontinued.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the promising results from the preclinical studies, the regimen of Sunitinib or Pazopanib combined with an anti-PD-1 antibody was largely offset by its excessive side effects (e.g., liver toxicity). Therefore, the combination with a more selective VEGFR-MKI, like Axitinib, has been investigated [91,92]. Although most of the clinical trials are still in the early phases, several international multi-centered randomized controlled trials (RCTs) have been conducted based on the tolerable dose and safety profile obtained from phase I/II trials.…”
Section: Rationale Of the Combined Therapymentioning
confidence: 99%